Legal regime of records management in Russian executive authorities - Olga V. Marchenko (Правоприменение)
The subject. Problems of legislative regulation of information and records management in executive authorities activity are raised.The purpose of the article is confirmation or confutation of the hypothesis that the lack of centralization of legal regulation of records management in Russian executive authorities causes problems in public governance.The methodology includes formal-legal method, systematic approach, formal-logical method, analysis, synthesis. The main results of research. The "legal regime of records management" is the established legal procedure for documenting information and organizing work with documents. The activity of executive authorities for the production of documented information has its own specifics. If analyze the normative legal acts, it can be stated that the system of legislation that regulates the implementation of documentation operations in the structure of executive authorities of the Russian Federation needs to be modified by specifying a number of existing provisions and including new ones.Conclusions. Despite the fact that currently there is a fairly developed regulatory framework for documentation management, a significant part of the issues related to the organization and technology of working with documents is not sufficiently regulated. In particular, this applies to the organization of electronic document management in the activities of executive authorities. The following measures could help to solve this and many other problems, and improve the state of documentation support for governance in the country: adaptation of international standards in the field of documentation maintenance of management to Russian conditions; restoration of state regulation of records management in executive authorities at all levels; creation of a federal executive authority responsible for improving, controlling, and regulating the documentation maintenance of governance; adoption of the federal law, which would fix the general principles and the most significant provisions of records management.